Quality analysis of financial statement reviews of local government: study of the impact of variables of time pressure and professional skills - Mulyati Akib; Tuti Dharmawati (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The main problems of this research were to test and analyze two independent variables, time pressure and professional skill, that related to the quality review of financial statements as a dependent variable. The data source used in this research was primary data, which is obtained from questionnaires. The questionnaires distributed to 36 respondents as the research sample. Those are internal auditor at Local Government of North Konawe and East Konawe. The data was analyzed by using Program Statistical Package for the Social Sciences (SPSS) Ver.22. The results show that time pressure and professional skills simultaneously have significant effect to the quality review of financial statement. Partially, time pressure has negative and significant effect to the quality review of financial statement, which means that if time pressure increases then the quality of review decreases, otherwise if time pressure decreases then the quality of the financial statement review increases. The result also indicated that professional skill has positive and significant effect to the quality review of financial statement. This means that if professional skill increases then the quality of the financial statement review will also increase and vice versa if the professional skill is low then the quality of the financial statement review will decrease.